An Augmented-Reality Device With Switchable Integrated Spaces Using a Bi-Focal Integral Floating Display - Minyoung Park; Kyung-Il Joo; Hak-Rin Kim; Hee-Jin Choi (IEEE Photonics Journal, 2019)
An augmented-reality (AR) device which presents virtual volumetric images to switchable integrated spaces is proposed and demonstrated. A bi-focal geometric phase (GP) lens can project the integrated volumetric images to switchable integrated spaces by switching the polarization of them. For that purpose, a combination of GP lens and an active polarization switching device has been adopted. A demonstration of an AR display with switchable integrations is also provided to verify the proposed concept.